2015
DOI: 10.1007/s00268-015-3261-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Clinical Outcomes of Recurrent Laryngeal Nerve Paralysis After Esophagectomy for Thoracic Esophageal Carcinoma

Abstract: RLNP developed in 60 % of patients after esophagectomy and may be associated with lymphadenectomy around the right RLN and cervical esophageal mobilization. Although 62% of affected nerves recovered within 12 months, great attention should be given when performing these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 39 publications
0
60
1
Order By: Relevance
“…Patients with RLNP may present with symptoms ranging from hoarseness, dyspnea during speech, aspiration, difficulty with coughing, marked morbidity through pulmonary complications [pneumonia, acute respiratory distress syndrome (ARDS), atelectasis], and may even suffocate in case of bilateral damage. Only few retrospective studies have reported on the consequences of RLNP on the short term, particularly the incidence of pulmonary complications (8)(9)(10)19,23,24). Furthermore, information on the long term (i.e., recovery and possible surgical interventions) is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with RLNP may present with symptoms ranging from hoarseness, dyspnea during speech, aspiration, difficulty with coughing, marked morbidity through pulmonary complications [pneumonia, acute respiratory distress syndrome (ARDS), atelectasis], and may even suffocate in case of bilateral damage. Only few retrospective studies have reported on the consequences of RLNP on the short term, particularly the incidence of pulmonary complications (8)(9)(10)19,23,24). Furthermore, information on the long term (i.e., recovery and possible surgical interventions) is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…For 6/21 of these patients surgical intervention (medialization thyroplasty) was required. All treatment interventions for vocal cord paralysis were conducted after a median time of 16.5 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] months after esophagectomy. Of all patients that underwent medialization thyreoplasty, 3/6 had no more RLNP symptoms afterwards 2/6 made a partial recovery from their RLNP, and 1/6 did not recover.…”
Section: Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus using hoarseness alone to diagnose RLN palsy will underestimate this complication. A review of three-field lymphadenectomy in Japan yielded an overall RLN palsy rate of 27% (20), some studies have shown up to 60% (1,21). In a recent detailed study on 299 patients, 60% developed RLN palsy, bilateral in 33%, right RLN in 8% and left in 59%.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the propensity of nodal spread along the recurrent laryngeal nerves (RLN), bilateral RLN nodal dissection is an important component of the operation. The RLN's are at risk of injury and the incidence of vocal cord paralysis after esophagectomy can be as high as 60% to 70% (1,2). In thyroidectomy, monitoring of RLN may reduce the chance of nerve injury.…”
Section: Introductionmentioning
confidence: 99%